2019
DOI: 10.1186/s12978-019-0775-9
|View full text |Cite
|
Sign up to set email alerts
|

Abortion experience and self-efficacy: exploring socioeconomic profiles of GHANAIAN women

Abstract: Background Unsafe abortions remain a major global public health concern and despite its prevalence, unsafe abortions remain one of the most neglected global health challenges. The proportion of women in Ghana who have experienced unsafe abortions has increased from 45% in 2007 to 62% in 2017. Given the noted consequences of (unsafe) abortions on women health, it is important to explore factors correlated with women’s abortion decisions and why they opt for safe or unsafe methods. The study also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 43 publications
5
16
1
Order By: Relevance
“…This study also showed that adolescent girls and young women who are exposed to mass media are more likely to have self-efficacy to make abortion decisions. This corroborates other studies on the association between mass media exposure and reproductive health decision-making capacities and behaviour in Ghana [9] and other parts of SSA [22]. Specifically, Owoo, Lambon-Quayefio and Onuoha, [9] found that mass media exposure has strong association with abortion self-efficacy among women in their reproductive age.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This study also showed that adolescent girls and young women who are exposed to mass media are more likely to have self-efficacy to make abortion decisions. This corroborates other studies on the association between mass media exposure and reproductive health decision-making capacities and behaviour in Ghana [9] and other parts of SSA [22]. Specifically, Owoo, Lambon-Quayefio and Onuoha, [9] found that mass media exposure has strong association with abortion self-efficacy among women in their reproductive age.…”
Section: Discussionsupporting
confidence: 90%
“…This corroborates other studies on the association between mass media exposure and reproductive health decision-making capacities and behaviour in Ghana [9] and other parts of SSA [22]. Specifically, Owoo, Lambon-Quayefio and Onuoha, [9] found that mass media exposure has strong association with abortion self-efficacy among women in their reproductive age. The probable explanation the authors gave to this association was that women who are exposed to mass media are more likely to be exposed to "western ideas and messages that encourage independence and greater autonomy".…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations